Recruiting endogenous stem cells: a novel therapeutic approach for erectile dysfunction - Zhong-Cheng Xin; Yong-De Xu; Guiting Lin; Tom F Lue; Ying-Lu Guo (Asian Journal of Andrology, 2016)
Transplanted stem cells (SCs), owing to their regenerative capacity, represent one of the most promising methods to restore erectile dysfunction (ED). However, insufficient source, invasive procedures, ethical and regulatory issues hamper their use in clinical applications. The endogenous SCs/progenitor cells resident in organ and tissues play critical roles for organogenesis during development and for tissue homeostasis in adulthood. Even without any therapeutic intervention, human body has a robust self-healing capability to repair the damaged tissues or organs. Therefore, SCs-for-ED therapy should not be limited to a supply-side approach. The resident endogenous SCs existing in patients could also be a potential target for ED therapy. The aim of this review was to summarize contemporary evidence regarding: (1) SC niche and SC biological features in vitro; (2) localization and mobilization of endogenous SCs; (3) existing evidence of penile endogenous SCs and their possible mode of mobilization. We performed a search on PubMed for articles related to these aspects in a wide range of basic studies. Together, numerous evidences hold the promise that endogenous SCs would be a novel therapeutic approach for the therapy of ED.